Perception, emotion, and synesthesia: Metaphorical combining in Keats - Brannon Katrina (ExELL (Explorations in English Language and Linguistics))
This article attempts to demonstrate the elaboration of poetic conceptual metaphor by way of perception verbs, emotion verbs, and expressions of synesthesia (sensorial mixing and blending). The instances of conceptual metaphor – various, but always emotionally based in nature – generally include expressions of force-dynamics, taking place within the emotional or psychosocial realm. The analyses, while focusing on a textual analysis as a whole, particularly concentrate on the grammatical and stylistic interplay between verbs and prepositions.